tan3xtan2xtanx=tan3x-tan2x-tanx

Asked by vaishaliklr | 6th Aug, 2010, 12:00: AM

Expert Answer:

Dear Student
Following is the solution of your question
consider
3x-2x=x
applying tanon both sides
tan(3x-2x) =tan x
(tan 3x- tan 2x)/(1+tan2xtan3x)=tan x
So tan 3x-tan 2x =tanx+tanxtan2xtan3x
i.e tan 3x-tan 2x -tanx=tanxtan2xtan3x
Hence proved
Regards
Team Topperlearning

Answered by  | 6th Aug, 2010, 09:14: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.